Begging for a title : an ethnographic research report on Zimbabwean blind beggars. - Katsande, Rukariro (My University, 2014)
The purpose of this research is to examine what blind begging is; why it exists; what it means; what causes it; and how beggars operate. It explores the theme that begging has evolved in Southern Africa through the influence of colonialism linked with institutionalised religion and traditional cultural conceptions: Christian, Muslim or Buddhist that equates giving, particularly to blind beggars, to receiving some form of salvation. The underlying theme is that blind beggars fulfil a requirement in society which satisfies a hierarchal social identity and the need to discard the excess or unwanted articles to those less fortunate in the guise of blind beggars. The hypothesis can be extended to the civilized west needing to be the developed and a polar opposite undeveloped Africa to which to donate and thus discard the excess or unwanted articles to appease some moral outlook but not to extract the blind beggar or underdeveloped state from poverty. Thus, blind begging is a professional response to a perceived market need and the blind beggars have the physical infrastructure to successfully exploit this niche market and thus make a sustainable livelihood that allows them to develop a business plan that guarantees a return that allows them to invest and eventually retire. I used a parachute method where I observed where the beggars operate and approached them for a focus group discussion, then individual interviews with participants. In Johannesburg they operate differently so I approached each beggar individually. This research is important to examine some lives of marginalised disabled in our society that may be misunderstood because of stereotypical social attitudes. It serves to highlight their plight and contribute to possible solutions to social mis-conceptions and practices. Most of the people I encountered giving donations made up the panel of givers.
Keywords: Blind Zimbabweans; Beggars; Begging